Anxiety in youth at clinical high risk for psychosis. Issue 6 (12th October 2015) - McAusland, Laina; Buchy, Lisa; Cadenhead, Kristin S.; Cannon, Tyrone D.; Cornblatt, Barbara A.; Heinssen, Robert; McGlashan, Thomas H.; Perkins, Diana O.; Seidman, Larry J.; Tsuang, Ming T.; Walker, Elaine F.; Woods, Scott W.; et al.
Abstract: Aim: High rates of anxiety have been observed in youth at clinical high risk (CHR) of developing psychosis. In CHR, anxiety often co‐occurs with depression, and there is inconsistent evidence on anxiety in relation to transition to psychosis. The aim of this study was to examine: (i) the prevalence of anxiety disorders in individuals at CHR; (ii) clinical differences between those with and without anxiety; and (iii) the association of baseline anxiety with later transition to psychosis. Methods: The sample consisted of 765 CHR individuals and 280 healthy controls. CHR status was determined with the Structured Interview of Prodromal Syndromes, mood and anxiety diagnoses with the Structured Clinical Interview for DSM‐IV Disorders, and severity of anxiety with the Social Interaction Anxiety Scale and Self‐Rating Anxiety Scale. Results: In the CHR sample, 51% met criteria for an anxiety disorder. CHR participants had significantly more anxiety diagnoses and severity than healthy controls. Anxiety was correlated to attenuated psychotic and negative symptoms in CHR and those with an anxiety disorder demonstrated more suspiciousness. CHR participants with obsessive–compulsive disorder (OCD) exhibited more severe symptomatology than those without OCD. An initial presentation of anxiety did not differ between those who did or did not transition to psychosis. Conclusions: In this large sample of individuals at CHR, anxiety is common and associated with more severe attenuated psychotic symptoms. Treatment not only to prevent or delay transition to psychosis but also to address presenting concerns, such as anxiety, is warranted.